Early Sialadenitis After Radioactive Iodine Therapy for Differentiated Thyroid Cancer: Prevalence and Predictors - Ruba Riachy; Nisrine Ghazal; Mohamad B. Haidar; Ahmad Elamine; Mona P. Nasrallah (International Journal of Endocrinology)
Introduction. Sialadenitis is a frequent occurrence after radioactive iodine therapy (RAI). However, reports on its predictors and risk factors in the Eastern Mediterranean Region (EMRO) are scarce. Aim. This study aimed to identify risk factors for early sialadenitis in patients receiving RAI for differentiated thyroid cancer (DTC) at the American University of Beirut Medical Center. It also aimed to determine the prevalence and characteristics of such patients receiving RAI at our institution. Methods. This was a retrospective study conducted at the American University of Beirut Medical Center. Medical charts were reviewed for all patients 18–79 years of age admitted to receive RAI for DTC between 01/01/2012 and 31/12/2015. Sialadenitis was deemed present if there were any records of neck swelling/pain, dry mouth, or difficulty swallowing within 48 hours of RAI administration. Characteristics between patients with sialadenitis and those without were compared to determine predictors. Results. There were 174 patients admitted to receive RAI, predominantly females (71.3%), with papillary thyroid cancer (93.1%). The majority had lymph node involvement (64.5%). Pretreatment thyroid stimulating hormone (TSH) was greater than 75 mIU/ml in most patients (72.6%). The prevalence of sialadenitis was 20.1% (95% CI (15–27)). Being non-Lebanese and having a positive whole-body scan were associated with sialadenitis and persisted after adjustments (OR = 2.34 and 3.99). Non-Lebanese patients had higher rates of lymph nodes involvement (p value 0.005) and were kept off levothyroxine for longer periods (p value 0.02). Conclusion. The prevalence of sialadenitis at our institution was similar to other reported studies from the world. However, risk factors allude to more iodine exposure in the neck with positive whole-body scan uptake, lymph node involvement, and prolonged period of hypothyroidism.